2007
DOI: 10.1016/j.cellsig.2007.03.010
|View full text |Cite
|
Sign up to set email alerts
|

GIT1 utilizes a focal adhesion targeting-homology domain to bind paxillin

Abstract: The GIT proteins, GIT1 and GIT2, are GTPase-activating proteins for the ADP-ribosylation factor family of small GTP binding proteins, but also serve as adaptors to link signaling proteins to distinct cellular locations. One role for GIT proteins is to link the PIX family of Rho guanine nucleotide exchange factors and their binding partners, the p21-activated protein kinases, to remodeling focal adhesions by interacting with the focal adhesion adaptor protein paxillin. We here identified the Cterminal domain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 54 publications
7
88
0
Order By: Relevance
“…In the absence of Src family kinases phosphorylating these sites, GIT2 is unable to localize to focal adhesions, whereas GIT1 shows no defect in localization (Brown et al 2005). We recently showed that GIT1 bearing mutations preventing tyrosine phosphorylation of these conserved sites is still able to bind paxillin (Schmalzigaug et al 2007). In endothelial cells, Garcia and colleagues reported distinct patterns of GIT1 and GIT2 phosphorylation and recruitment to adhesions in response to cell activation (Shikata et al 2003b).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of Src family kinases phosphorylating these sites, GIT2 is unable to localize to focal adhesions, whereas GIT1 shows no defect in localization (Brown et al 2005). We recently showed that GIT1 bearing mutations preventing tyrosine phosphorylation of these conserved sites is still able to bind paxillin (Schmalzigaug et al 2007). In endothelial cells, Garcia and colleagues reported distinct patterns of GIT1 and GIT2 phosphorylation and recruitment to adhesions in response to cell activation (Shikata et al 2003b).…”
Section: Discussionmentioning
confidence: 99%
“…The coiledcoil domain is responsible for dimerization of GIT proteins by forming a parallel coiled-coil Schlenker and Rittinger, 2009). The FAT domain is a four-helix bundle and the binding site for the focal adhesion adaptor protein paxillin in a manner that is similar to paxillin binding to the FAT domain of focal adhesion kinase (Schmalzigaug et al, 2007a;Zhang et al, 2008).…”
Section: Git Proteinsmentioning
confidence: 99%
“…GITs are also prominent substrates for Src family kinases (Haendeler et al, 2000;Brown et al, 2005;Heckel et al, 2009). Src/FAK-mediated phosphorylation of GIT2 at amino acid residues Y286, Y392 and Y592 is required for binding to paxillin at focal adhesions (Brown et al, 2005) but the cognate residues in GIT1 are not necessary for paxillin association (Schmalzigaug et al, 2007a). However, both GIT1 and GIT2 phosphorylated at Y392 bind to the SH2-SH3 adaptor proteins Nck1 and Nck2 (Frese et al, 2006;Segura et al, 2007).…”
Section: Git-pix Complexes: a Node For Signal Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The QuikChange TM Site-Directed Mutagenesis kit (Stratagene) was used to generate point mutants of Cat-1 that are defective in binding Cool-1 (D294K/E295R) (24), paxillin (K663E/K758E) (25), or are defective as an Arf-GAP (R39A) (26). Likewise, dominant active forms of Arf1 (Q71L, T161A) (27,28) and Arf6 (D125N) (29), as well as dominant negative Arf6 (T27N) (30), were also generated.…”
Section: Methodsmentioning
confidence: 99%